Design and synthesis of fluconazole/bile acid conjugate using click reaction - Pore, Vandana S.; Aher, Nilkanth G.; Kumar, Manish; Shukla, Praveen K. (Tetrahedron, 2006)
Novel fluconazole/bile acid conjugates were designed and their regioselective synthesis was achieved in very high yield via Cu(I) catalyzed intermolecular 1,3-dipolar cycloaddition. These new molecules showed good antifungal activity against Candida species. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: 1; 2; 3-Triazole; Antifungal agent; bile acid; Click chemistry; fluconazole/bile acid conjugate

Triton X-114 fractionated subcellular proteome ofleptospira interrogansshows selective enrichment of pathogenic and outer membrane proteins in the detergent fraction - Thoduvayil, Sikha; Dhandapani, Gunasekaran; Brahma, Rahul; Devasahayam Arokia Balaya, Rex; Mangalaparthi, Kiran K.; Patel, Krishna; Kumar, Manish; Tennyson, Jebasingh; Satheeshkumar, P. K.; Kulkarni, Mahesh J.; Pinto, Sneha M.; Prasad, T. S. Keshava; et al. (Proteomics, 2020)
The Triton X-114-based solubilization and temperature-dependent phase separation of proteins is used for subcellular fractionation where, aqueous, detergent, and pellet fractions represents cytoplasmic, outer membrane (OM), and inner membrane proteins, respectively. Mass spectrometry-based proteomic analysis of Triton X-114 fractions of proteomic analysis ofLeptospira interrogansidentified 2957 unique proteins distributed across the fractions. The results are compared with bioinformatics predictions on their subcellular localization and pathogenic nature. Analysis of the distribution of proteins across the Triton X-114 fractions with the predicted characteristics is performed based on ``number'' of unique type of proteins, and ``quantity'' which represents the amount of unique protein. The highest number of predicted outer membrane proteins (OMPs) and pathogenic proteins are found in aqueous and pellet fractions, whereas detergent fraction representing the OM has the highest quantity of OMPs and pathogenic proteins though lower in number than the aqueous and pellet fractions. This leaves the possibility of an upsurge in pathogenic proteins and OMPs on the OM under pathogenic conditions suggesting their potential use to combat leptospirosis. Further, the Triton X-114 subcellular fractions are more correlated to enrichment of pathogenic proteins predicted by MP3 software than predicted localization.
Keywords: intensity-based absolute quantification; Leptospira; outer membrane protein; subcellular localization; Triton X-114

Alpha-angelica lactone catalyzed oxidation of pyrrolidines to lactams - Deepake, Siddharth K.; Kumar, Manish; Kumar, Pawan; Das, Utpal (European Journal of Organic Chemistry, 2022)
Herein, we report an efficient protocol for the synthesis of gamma-lactams from pyrrolidines and oxygen. The strategy follows a two-step process involving an initial generation alpha-amino alkyl radicals from pyrrolidines and oxygen in presence of 4-dimethylaminopyridine (DMAP) followed by trapping of the radical with oxygen species. This protocol demonstrates good functional group acceptance and provides a direct method to access gamma-lactams. The lactam derivatives were obtained in up to 98 % yield.
Keywords: alpha-Amino alkyl radicals; alpha-Angelica lactone; lactams; Oxidation; Pyrrolidines

Radical cascade cyclization of unactivated alkene-tethered indoles with aryldiazonium salt and sodium metabisulfite to access Azo- and Sulfonylated-2,3-Dihyro-1H-pyrrolo[1,2-a]indoles - Kumar, Pawan; Rai, Archana; Kumar, Manish; Krishna, Gamidi Rama; Das, Utpal (Journal of Organic Chemistry, 2023)
A method for the construction ofheterocyclic scaffold2,3-dihyro-1H-pyrrolo[1,2-a]indolesvia arylsulfonylradical-triggered cascade cyclization of unactivated alkene-tetheredindoles in the absence of any external photocatalyst has been developed.This protocol features easily accessible starting materials such assodium metabisulfite and aryldiazonium tetrafluoroborates at roomtemperature and offers good functional group compatibility, enablingthe introduction of various functionalized sulfonyl and azo groupsinto pyrrolo[1,2-a]indoles.

Synthesis of N-functionalized 2,3-disubstituted benzofurans/naphthofurans from para-quinone methides and isocyanides via the [4+1] annulation pathway - Kale, Someshwar B.; Kumar, Manish; Shinde, Dinesh R.; Krishna, Gamidi Rama; Das, Utpal (Organic Chemistry Frontiers, 2023)
A scandium triflate catalyzed [4 + 1] cycloaddition reaction of 2-hydroxy-substituted para-quinone methides and isocyanides has been developed. This operationally simple, efficient and practical protocol provides straightforward access to a variety of N-functionalized 2,3-disubstituted benzofuran/naphthofuran derivatives with broad functional group compatibility and good scalability.

Photocatalytic oxidation of α-substituted amines to lactams/amides - Kumar, Manish; Kumar, Pawan; Das, Utpal (Advanced Synthesis & Catalysis, 2025)
We, herein, report a base free, photocatalytic decyanation of alpha-aminonitriles. A range of amides and lactams were obtained in 52-95% yields. Control experiments indicate O2 as an amide/lactam oxygen source and the reaction (lactam formation) follows radical pathway via dioxetanimine species. This methodology also applied for alpha-ester/aldehyde substituted pyrrolidines in the presence of a base, probably via decarboxylation pathway.
Keywords: alpha-Aminonitriles; Decyanation; Dioxetanimine; Photocatalytic; pyrrolidine

Synthesis of benzannulated [5,6] oxa-fused/spiro-lactones via [4+2] cycloaddition with quinone methides: new insights into deconjugated butenolide reactivity - Kumar, Manish; Kale, Someshwar B.; Jawahar, Subramani; Barkade, Apurva D.; Das, Utpal (Journal of Organic Chemistry, 2025)
In this study, we unfold a Lewis-acid-catalyzed inverse electron demand hetero Diels-Alder (IEDHDA) [4 + 2] reaction, leveraging the unique beta-selective nucleophilicity of deconjugate lactone in conjunction with quinone methides for the synthesis of polycyclic fused and spiro acetals in a one-pot process. This cascade annulation reaction efficiently generates 3/4 chiral centers with high diastereoselectivity. The developed methodology proceeds under mild reaction conditions and exhibits a broad substrate scope for fused and spiro acetal formation.